Practice Effects and Test–Retest Reliability of the Continuous Performance Test, Identical Pairs Version in Patients with Schizophrenia over Four Serial Assessments. (22nd February 2020) - Chen, Kuan-Wei; Lin, Gong-Hong; Chen, Nan-Cheng; Wang, Ji-Kuan; Hsieh, Ching-Lin
Abstract: Objective: The purposes of this study were to examine the practice effects and test–retest reliability of the Continuous Performance Test, Identical Pairs version (CPT-IP) over four serial assessments in patients with schizophrenia. Method: Fifty-six patients with schizophrenia were assessed with the CPT-IP four times, once per week. The CPT-IP contains four indices: "2-digit score, " "3-digit score, " "4-digit score, " and "total score." Results: The four indices showed trivial-to-small practice effects (Cohen's d  = −0.13–0.24), good-to-excellent test–retest reliability (ICC = 0.62–0.88), and unacceptable random measurement error (MDC% = 33.8%–110.8%). Conclusions: The total score had the best reliability among the four indices. Although practice effects of the four indices all appeared cumulative, all four CPT-IP indices reached a plateau after the second assessment. These results indicate that clinicians should interpret the change scores of the CPT-IP conservatively and use the total-score index in their routine repeated assessments.